Survival motor neuron deficiency slows myoblast fusion through reduced myomaker and myomixer expression. Issue 4 (11th June 2021) - McCormack, Nikki M.; Villalón, Eric; Viollet, Coralie; Soltis, Anthony R.; Dalgard, Clifton L.; Lorson, Christian L.; Burnett, Barrington G.
Abstract: Background: Spinal muscular atrophy is an inherited neurodegenerative disease caused by insufficient levels of the survival motor neuron (SMN) protein. Recently approved treatments aimed at increasing SMN protein levels have dramatically improved patient survival and have altered the disease landscape. While restoring SMN levels slows motor neuron loss, many patients continue to have smaller muscles and do not achieve normal motor milestones. While timing of treatment is important, it remains unclear why SMN restoration is insufficient to fully restore muscle size and function. We and others have shown that SMN‐deficient muscle precursor cells fail to efficiently fuse into myotubes. However, the role of SMN in myoblast fusion is not known. Methods: In this study, we show that SMN‐deficient myoblasts readily fuse with wild‐type myoblasts, demonstrating fusion competency. Conditioned media from wild type differentiating myoblasts do not rescue the fusion deficit of SMN‐deficient cells, suggesting that compromised fusion may primarily be a result of altered membrane dynamics at the cell surface. Transcriptome profiling of skeletal muscle from SMN‐deficient mice revealed altered expression of cell surface fusion molecules. Finally, using cell and mouse models, we investigate if myoblast fusion can be rescued in SMN‐deficient myoblast and improve the muscle pathology in SMA mice. Results: We found reduced expression of the muscle fusion proteins myomaker ( P = 0.0060) and myomixer ( P = 0.0051) in the muscle of SMA mice. Suppressing SMN expression in C2C12 myoblast cells reduces expression of myomaker (35% reduction; P < 0.0001) and myomixer, also known as myomerger and minion, (30% reduction; P < 0.0001) and restoring SMN levels only partially restores myomaker and myomixer expression. Ectopic expression of myomixer improves myofibre number (55% increase; P = 0.0006) and motor function (35% decrease in righting time; P = 0.0089) in SMA model mice and enhances motor function (82% decrease in righting time; P < 0.0001) and extends survival (28% increase; P < 0.01) when administered in combination with an antisense oligonucleotide that increases SMN protein levels. Conclusions: Here, we identified reduced expression of muscle fusion proteins as a key factor in the fusion deficits of SMN‐deficient myoblasts. This discovery provides a novel target to improve SMA muscle pathology and motor function, which in combination with SMN increasing therapy could enhance clinical outcomes for SMA patients.